Effect of Pulsed Electric Field on Membrane Lipids and Oxidative Injury of Salmonella typhimurium - Yun, Ou (Int J Mol Sci, 2016)
Salmonella typhimurium cells were subjected to pulsed electric field (PEF) treatment at 25 kV/cm for 0–4 ms to investigate the effect of PEF on the cytoplasmic membrane lipids and oxidative injury of cells. Results indicated that PEF treatment induced a decrease of membrane fluidity of Salmonella typhimurium (S. typhimuriumi), possibly due to the alterations of fatty acid biosynthesis-associated gene expressions (down-regulation of cfa and fabA gene expressions and the up-regulation of fabD gene expression), which, in turn, modified the composition of membrane lipid (decrease in the content ratio of unsaturated fatty acids to saturated fatty acids). In addition, oxidative injury induced by PEF treatment was associated with an increase in the content of malondialdehyde. The up-regulation of cytochrome bo oxidase gene expressions (cyoA, cyoB, and cyoC) indicated that membrane damage was induced by PEF treatment, which was related to the repairing mechanism of alleviating the oxidative injury caused by PEF treatment. Based on these results, we achieved better understanding of microbial injury induced by PEF, suggesting that micro-organisms tend to decrease membrane fluidity in response to PEF treatment and, thus, a greater membrane fluidity might improve the efficiency of PEF treatment to inactivate micro-organisms.